An investigation of institutional analysis on managing reservoir environment was carried out at Jatiluhur reservoir, West Java. Data were collected from several institution which relates to reservoir environment management in relation to the floating fish cage culture practises. Descriptive method was used to analyze the institutional aspects on manging reservoir environment which relates to the floating cage culture practises. The results of the research showed that the institution roles are go - Zahri Nasution (Buletin Ekonomi Perikanan, 2005)
An investigation of institutional analysis on managing reservoir environment was carried out at Jatiluhur reservoir, West Java. Data were collected from several institution which relates to reservoir environment management in relation to the floating fish cage culture practises. Descriptive method was used to analyze the institutional aspects on manging reservoir environment which relates to the floating cage culture practises. The results of the research showed that the institution roles are good enough in managing reservoir environment in relation to the floating fish cage culture. Each of institution was funtioning it's tasks and authorities based on their yurisdiction respectively. The right and obligation of the institutions had been function based on their task and authority except the informatin of the water changes for fish farmers are not available yet. In addition, the fish farmers representation were not included as a member of the fisheries advise: team of Director of the POJ on Fisheries Section. All of institution have the same perception on reservoir environment management in relation to fish farmer cage culture practises.